Parallel Electrostatic Waves Associated With Turbulent Plasma Mixing in the Kelvin‐Helmholtz Instability. Issue 14 (13th July 2020) - Wilder, F. D.; Schwartz, S. J.; Ergun, R. E.; Eriksson, S.; Ahmadi, N.; Chasapis, A.; Newman, D. L.; Burch, J. L.; Torbert, R. B.; Strangeway, R. J.; Giles, B. L.
Abstract: The Kelvin‐Helmholtz Instability (KHI) is thought to be an important driver of mass and momentum transfer from the solar wind to the Earth's magnetosphere. We present observations from NASA's Magnetospheric Multiscale mission of ion acoustic‐like waves associated with turbulence during the KHI interval on 8 September 2015. These parallel electrostatic waves are nonlinear, can have amplitudes in excess of 100 mV/m, and may be associated with a field‐aligned potential drop. We perform a survey of all vortices in the 8 September 2015 event, investigating the occurrence of electrostatic waves below the ion plasma frequency. We find that they tend to occur in the turbulent region in the middle of the KHI vortices, independent of the presence of compressed or intermittent currents. This suggests that the waves occur in the presence of plasma mixing in the vortex region and that they may play a part in the overall turbulent dissipation process. Key Points: Ion‐acoustic‐like waves occur within the Kelvin‐Helmholtz instability at Earth's magnetosphere These waves appear in the vortex regions of the Kelvin‐Helmholtz instability and are not related to electric currents These waves are potentially due to mixing of plasma populations and may impact the turbulent dissipation process